Effect of Insecticides on Sucking Pests and Arthropod Predators in Rainfed Bt Cotton - MEGHANA, H.; JAGGINAVAR, S. B.; SUNITHA, N. D. (Cotton Research Journal, 2021)
A study was conducted to know the bioefficacy of different insecticides on sucking pests of Bt cotton under rainfed situation at College of Agriculture, Vijayapur. Flonicamid 50 WG was highly effective in minimizing thrips followed by Fipronil 5 SC. Biopesticide Lecanicilium lacanii recorded minimum thrips population. Similar effect was there also on aphids and leafhoppers. Thiamethoxam 25 WG was observed as safest insecticide followed by Diafenthiuron 50WP, Fipronil 5SC and Acetamiprid 20 SP to the lady bird beetles and green lace wings, however Diafenthiuron 50WP was safer to spidrs followed by Thiamethoxam 25 WG, Fipronil 5SC and Acetamiprid 20 SP. Significantly highest seed cotton yield was harvested from Flonicamid 50 WG treatment (25.13 q/ha) followed by Fipronil 5 SC (23.95 q/ha), Dinotefuran 20 SG (23.36 q/ha) and Acetamiprid 20 SP (23.05 q/ha) and these are at par with each other. L. lecanii treatment yielded 15.52 q/ha. Cost economics of different treatments revealed that among the chemical treatments, highest benefit cost ratio was obtained in Fipronil 5 SC followed by Acetamiprid 20 SP and Flonicamid 50 WG.